A preparation technology of volatile components in Linggui Zhugan decoction based on the transfer of cinnamaldehyde and its anti-gastric ulcer effect - Ling Li; Nan Wang; Xiaolong Fan; Ning He; Tong Zhang (Saudi Pharmaceutical Journal, 2023)
Purpose: This study aims to preserve the volatile components of Linggui Zhugan (LGZG) decoction, offering an experimental foundation for subsequent preparations efforts. Methods: Two modern sample preparation processes were compared with the traditional method approach using HPLC fingerprints. After identifying the main volatile components in LGZG aqueous decoction, the inclusion method of inclusion compounds (IC-LGZG) was established and optimized at laboratory, pilot and production scales. Characterization, stability testing of IC-LGZG, and experiments on gastric ulcer rats were conducted to validate the transferability of chemical composition and pharmaceutical efficacy. Results: The study focused on preserving the volatile components in LGZG modern preparations. HPLC analysis revealed cinnamaldehyde (CA) as the main volatile component in LGZG decoction. The optimized IC-LGZG preparation involved heating aromatic water to 40 °C, adding 20 g/L of β-Cyclodextrin (β-CD), keeping warm and stirring at 300 r for 30 min. This process exhibited good repeatability across different verification tests at varying scales. IC-LGZG obtained effectively transferred CA molecules into the β-CD molecules via encapsulation, remaining stable when stored in sealed and dark conditions. Finally, CA, IC-LGZG and M−LGZG (a mixture of IC-LGZG and water-soluble extract powder) effectively prevented the formation of gastric ulcer by mitigating reductions in IL-10, SOD and the increase of TNF-α, NO, MDA in serum. Conclusion: The IC-LGZG prepared using this process successfully transfers volatile components, both chemically and pharmacologically, making it suitable for modern preparations of LGZG.